Penggunaan Teori Kognitivisme dalam Proses Pembelajaran di MIN 1 Lebong - Dewi, Nurhayani; Sari, Purnama (Program Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah dam Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2022)
The theory provided many of the key concepts in the field of developmental psychology and influenced the development of the concept of intelligence, which for Piaget meant the ability to more accurately represent the world and perform logical operations on representations of concepts based on reality. This theory concerns the emergence and acquisition of schemata about how a person views the world during the developmental stage, when a person acquires new ways of representing information mentally. This theory is classified as constructivism, meaning that, unlike nativism theory (which describes cognitive development as the display of innate knowledge and abilities), it argues that we build our cognitive abilities through self-motivated actions on the environment.